2011
DOI: 10.1007/bf01616346
|View full text |Cite
|
Sign up to set email alerts
|

Decreased intracellular phosphate and magnesium concentrations in vascular smooth muscle cells from spontaneously hypertensive rats

Abstract: A decrease in total magnesium content is not a direct proof of a decreased magnesium ion concentration. It could reflect a phosphate alteration or an ATP metabolism disorder. Plasma phosphate levels are lower in spontaneously hypertensive rats (SHR) than in Wistar-Kyoto rats (WKY), and defects in membrane regulation or mitochondrial ATP synthase occur. Only sparse data exist concerning cellular magnesium and phosphate concentrations in hypertensive cells. In aortic smooth muscle cells from 10 SHR of the Münste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Erythrocyte membrane fluidity depends on Na + ,K + -ATPase activity, which is reduced in hypertensive patients [16] and in spontaneously hypertensive rats [6]. The mechanisms underlying such reduction are still obscure, but it has been reported that plasma membrane Na + ,K + -ATPase may be inhibited by ouabain-like endogenous inhibitors [5], which are decreased by physical exercise [17] or antihypertensive agents, which can enhance Na + ,K + -ATPase activity [10]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erythrocyte membrane fluidity depends on Na + ,K + -ATPase activity, which is reduced in hypertensive patients [16] and in spontaneously hypertensive rats [6]. The mechanisms underlying such reduction are still obscure, but it has been reported that plasma membrane Na + ,K + -ATPase may be inhibited by ouabain-like endogenous inhibitors [5], which are decreased by physical exercise [17] or antihypertensive agents, which can enhance Na + ,K + -ATPase activity [10]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that biochemical and biophysical abnormalities of cell membranes [5] may actively participate in the pathogenesis of hypertension [6], and that such abnormalities seem to be involved not only in vascular smooth muscle cells, but also in circulating blood cells [7]. In fact, it has been reported that viscosity and rigidity of erythrocyte membranes are increased in spontaneously hypertensive rats (SHR) and in patients with essential hypertension [8], and that erythrocyte membrane fluidity depends on Na + ,K + -ATPase activity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to our knowledge, this is the first study to investigate the effect of long-term OUA in vascular Na + , K + -ATPase activity in a model of essential hypertension. It was demonstrated that aortic smooth muscle cells from SHRs have diminished Na + , K + -ATPase activity [33]. However, endothelium-derived factors can be released from the aorta of normotensive and SHRs in the presence of OUA, which could activate Na + , K + -ATPase activity [24,34,35].…”
Section: Enos Nnos and Cox-2 Protein Expressionmentioning
confidence: 98%